Isolasi Bakteri Pendegradasi Limbah Cair Industri Minyak Sawit - Monica Kharisma Swandi; Periadnadi Periadnadi; Nurmiati Nurmiati (Universitas Andalas, 2015)
An isolation of degrading bacteria of Palm Oil Mill Effluent (POME) was conducted from May to October 2014 at the Laboratory of Microbiology, Department of Biology, Faculty of Natural Sciences, Andalas University. This study aimed to describe the characteristic of the bacteria which can degradate the POME. The result obtained five isolates ie BLS1, BLS2, BLS3, BLS4 and BLS5 and their characters were rod-shaped (basil), gram-positive, motile, positive catalase and forming endospores. Keywords: isolation, characterization, degrading bacteria, POME